Risk of Thromboembolism in Non-Valvular Atrial Fibrillation With or Without Clinical Hyperthyroidism. Issue 1 (17th June 2021) - Lin, Yu-Sheng; Tsai, Hsin-Yu; Lin, Chia-Ying; Wu, Victor Chien-Chia; Chen, Tien-Hsing; Yang, Teng-Yao; Aboyans, Victor; Chen, Mien-Cheng
Background: Patients with hyperthyroidism have higher risk of atrial fibrillation (AF). However, the risk of thromboembolic event in patients with hyperthyroidism-related AF is controversial. Objectives: The aim of the study was to examine the risk of thromboembolic events in AF patients with/without hyperthyroidism. Methods: The national retrospective cohort study enrolled AF population was derived from the Taiwan National Health Insurance Research Database. The comparison between the AF patients with clinical hyperthyroidism (HT-AF group) and AF patients without hyperthyroidism (non-thyroid AF group) was made in a propensity score matched cohort and in a real-world setting, of which, the CHA2 DS2 -VASc level was treated as a stratum variable. The outcomes were ischemic stroke and systemic thromboembolism. Results: There were 3, 880 patients in HT AF group and 178, 711 in non-thyroid AF group. After propensity score analysis, the incidence of thromboembolism event and ischemic stroke were lower in HT AF patients than non-thyroid AF patients (1.6 versus 2.2 events per 100 person-years; HR, 0.73; 95% CI, 0.64–0.82 and 1.4 versus 1.8 events per 100 person-years; HR, 0.74; 95% CI, 0.64–0.84, respectively) in the 4.3 ± 3.2 year follow up period. The differences persistently existed in those receiving anticoagulants or not. In AF patients without anticoagulants, the incidence densities of ischemic stroke/systemic thromboembolism were significantly lower in HT AF group than those in non-thyroid AF group at CHA2 DS2 -VASc scores ≤ 4 (HR, 0.41; 95% CI, 0.35–0.48, p < 0.001), while the differences disappeared in case of score ≥ 5 (HR, 0.80; 95% CI, 0.63–1.02, p = 0.071). Conclusion: Patients with HT AF had lower incidence of thromboembolic events as compared to non-thyroid AF patients. The threshold of CHA2 DS2 -VASc score for anticoagulation in AF patients with clinical hyperthyroidism should be further evaluated. Highlights: The incidence of thromboembolic event was different between hyperthyroidism-related atrial fibrillation (HT-AF) and non-thyroid AF patients. Hyperthyroidism did not confer additional risk of thromboembolic event at CHA2 DS2 -VASc of ≤ 4. The benefit of anticoagulation strategy in patients with hyperthyroidism-related AF should be further evaluated, especially at low CHA2 DS2 -VASc score.